Fermentado de laranja composto de extrato de ervas aromáticas: desenvolvimento, caracterização e avaliação do potencial biológico - Mascarin, Laura Gizele (2023)
Consumers have been increasingly interested in beverages that, in addition to being differentiated in flavor, can provide health benefits. To achieve this, the industry is challenged to develop mainly functional products, rich in bioactive compounds. In this sense, fermentation is an important tool in the production of functional beverages from antioxidant-rich fruits, medicinal and aromatic plants, since the ethanolic medium contributes to the extraction and bioavailability of bioactive compounds that protect against the incidence of many diseases of modern society. Citrus fruits are generally known to have a low shelf life and face the problem of post-harvest losses. Efforts have therefore been made to explore the potential of these fruits in the development of alcoholic beverages. Therefore, this study developed a fermented orange beverage and evaluated the contribution of the addition of extracts of Matricaria recutita (chamomile), Cymbopogon citratus (lemongrass) and Mentha piperita (peppermint) to the phytochemical profile and the potential in vitro, in silico, and in vivo biological effects. Sensory analysis determined that beverages with the addition of 2% of aromatic herb extracts obtained the best acceptability, so this concentration of extracts was used in subsequent assays. In vitro characterization analyses showed that the addition of aromatic herb extracts contributed to a higher content of phenolics, flavonoids, and antioxidant potential compared to the control beverage. The main bioactive compounds present in the formulations were hesperidin (124-130 mg L-1), narirutin (66-70 mg L-1), chlorogenic acid (11-16 mg L-1), caffeic acid (5.3-5.5 mg L-1), and ferulic acid (1-1.7 mg L-1). In silico analysis indicated that these compounds do not present a risk of toxicity (mutagenicity, carcinogenicity, hepatotoxicity, and ability to penetrate the blood-brain barrier). In addition, in silico assays indicated that these compounds can contribute to biological effects of therapeutic importance, such as antioxidant, gastroprotective, and antiulcerative, with the extract of M. piperita showing greater potential among the herbs evaluated for use in functional fermented products. In vivo analysis was performed through a model of ethanol-induced gastric ulcer (EtOH) in rats. Histopathological evaluation showed that EtOH administration resulted in the formation of gastric ulcers due to the reduction of the mucous layer, presence of hemorrhage, and infiltration of neutrophils in the stomach tissue of rats, and the treatment with different orange fermented beverages was not able to reverse these changes. In addition, EtOH administration altered the volume of gastric juice and induced oxidative stress in stomach tissue, observed through the increase in lipid peroxidation (TBARS), reduction of non-protein thiols (SHNP) levels, and alteration of superoxide dismutase (SOD) activity. Consumption of the fermented orange beverage (control) increased SHNP levels and reduced changes in TBARS levels induced by EtOH. Therefore, these findings suggest that the fermented orange beverage has antioxidant effects, as indicated by in silico studies, but not gastro repair and antiulcerative effects. Future studies can be conducted to investigate the gastroprotective effect of fermented and also non-alcoholic beverages.